PENYULUHAN MENJAGA KESEHATAN MATA ANAK SELAMA PEMBELAJARAN DARING DI MASA PANDEMIK COVID-19 - Kartini Kartini; Amalia H; Zaina N A; Yenny Yenny; Angraeni C (JUARA: Jurnal Wahana Abdimas Sejahtera, 2021)
The Covid-19 pandemic that hit Indonesia affects almost all aspects of our lives including in education where learning patterns turn into online learning. Strain on the eyes can cause discomfort and may lead to decreased productivity. The purpose of this counseling is to improve the understanding of maintaining the health of children's eyes in this period of online learning by applying the pattern of use of gadgets properly and correctly.  The results of this activity showed that there was an increasing the knowledge of participants. Before counseling, only 4.5% of participants had good knowledge about how to maintain eye health. After being given counseling, the level of good knowledge of the participants increased to 60%. Pay attention to ergonomic sitting positions such as computers/laptops are placed in line with the eye view and optimal room lighting settings are performed as good lighting supports eye health. Get used to giving enough time for the body to rest periodically for example resting the eyes every 2 hours after the use of the gadget. The frequency of rest after using a computer is proven to increase comfort and relax the power of eye accommodation. When resting your eyes it is recommended to do physical activity outdoors to be exposed to sunlight. In addition, it is necessary to maintain the health of the eyes from the inside by eating nutritious and vitamints, such as vegetables and colored fruits